Phosphinous Acid Platinum Complex as Robust Catalyst for Oxidation: Comparison with Palladium and Mechanistic Investigations. Issue 39 (11th October 2018) - Membrat, Romain; Vasseur, Alexandre; Martinez, Alexandre; Giordano, Laurent; Nuel, Didier
Abstract : Secondary phosphine oxides proved to be effective preligands to stabilise a hydroxy‐platinum based catalyst that allows the aerobic/anaerobic oxidation of challenging substrates. Kinetic comparisons showed that this system is more efficient and stable than previously reported similar palladium‐based catalysts. A neutral platinum dimer bearing bridging hydroxy ligands has been isolated and fully characterised by X‐ray diffraction and its involvement in the mechanism has been evidenced by mechanistic studies. Abstract : The use of phosphinous acids as ligands of palladium or platinum complexes allows the formation of very stable catalytic systems. Efficient anaerobic oxidation of unreactive alcohols is achieved without degradation of the catalyst. Mechanistic investigations give evidence of the implication of a platinum hydroxyl species.